Elaboración de plan de mejoramiento de equipos para el laboratorio de refrigeración y acondicionamiento de aire de la universidad (2018)
For the development of the project that has as name elaboration of equipment improvement plan for the laboratory of refrigeration and air conditioning of the university; Initially a diagnosis was made of the 7 teams involved in the project which are: Refrigeration teaching module, Heat pump teaching module, Window type air conditioning training module, No-frost fridge teaching module, Freezing training module and mobile air conditioning module; in order to determine the initial state of each one. At the time of diagnosis and initial data collection in the teams, several inconsistencies were determined both visually and in their operation, which is why an intervention procedure was carried out, which consisted of a system sweep by means of nitrogen gas, and a recharge using the same type of refrigerant, to subsequently perform a new data collection and thus determine the correct functionality of both the system and each of its components.